Damping of Low-Frequency Oscillations by Supplementary Control of Power System Stabilizers - Febres, C.A.T.; Araujo, P.B.; Furini, M.A. (Trends in Computational and Applied Mathematics, 2008)
This work presents studies of the small signal stability applied to an electric power system with the consideration of the Power System Stabilizer in operation. The Power Sensitivity Model is used to represent the electric power system. Information about the stability of the electric power system when subjected to small disturbances is obtained simulating a test system.